Fashion rental contracts: legal framework in Spain and the United States from a comparative perspective - Ortega Burgos, Enrique (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Fashion rental has emerged as a growing trend in the textile industry. This article offers a comparative analysis of the legal framework governing fashion rental contracts in Spain and the United States, with a focus on their legal nature, contractual obligations, common clauses, and consumer protection mechanisms. Despite the differences between both legal systems, there is an increasing degree of practical convergence, although notable disparities remain in terms of abusive clause control and the level of consumer protection. The study highlights the legal challenges posed by this contractual model and proposes a framework for mutual learning between the two jurisdictions.
Keywords: Fashion rental; lease contract; consumer protection; unfair terms; comparative law; Spain; United States; sharing economy